V-045 SAFENESS OF LIQUIBAND FIX8® IN T.A.P.P. PROCEDURE: ANALYSIS OF COSTS, POST-OPERATIVE COMPLICATIONS AND RECURRENCES. (13th October 2022) - Latham, L; Ballabio, A; Monti, E; Costa, J; Marzorati, A; Colombo, E M; Odeh, M; Garbarino, S; Gianazza, S; Inversini, D; Ietto, G; Carcano, G
Abstract: Aims: We tested the use of LiquiBand®FIX8™ versus standard TAPP procedure comparing costs, surgical time, complications, recurrence rate, chronic pain to check the feasibility of the procedure. Materials and Methods: LiquiBand®FIX8™is a cyanoacrylic adhesive used to fix the mesh during laparoscopic procedures. It consents the avoidance of plastic or metallic fixing materials that can causes post-operative chronic pain or vascular damage Discussion: We performer 54 TAPP procedures, 48 with standardized tack technique and 6 with LiquiBand®FIX8™. We checked the results after a 6 months follow-up and we found no difference in recurrence rate or chronic pain between the two techniques. Costs and surgical time were inferior in LiquiBand®FIX8™ group. Conclusions: The use of LiquiBand®FIX8™is a safe and feasible procedure during TAPP to reduce the surgical time, to limit costs and to avoid intraoperative and postoperative complications that can occur with mechanical fixing materials.